Developing Beef Cattle in Banyumas Regency: Potentials and Strategies - Nunung Noor Hidayat; Krismiwati Muatip; Rahayu Widiyanti (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2021)
Optimum development of beef cattle is feasible in the potential area with effective strategies. This research was conducted in Banyumas regency. The purpose of this study was to describe the potential of Banyumas Regency in developing beef cattle farming as the basis for its development strategy. A survey method was conducted to obtain the secondary data supported by primary data subjected to simple descriptive statistical analysis consisting of mean values, distribution frequency, cross-tabulation and trend analysis. Ruminant potentials were investigated using LQ analysis, and developmental strategies were formulated using a SWOT analysis. The result showed a fluctuated but positive improvement trend of beef cattle population in Banyumas. Sub-districts potentially developed for beef cattle centres (LQ>1) included Kembaran, Sokaraja, Kalibagor, Kedungbanteng, Karanglewas, Sumbang and Baturraden. A quantitative SWOT matrix analysis showed that the internal factor was 0.0298 (X-axis), and the external factor was – 0.2941 (Y-axis). Conclusively, The key strategy to develop beef cattle in Banyumas was a differential strategy.